Sistem Seat Allotment Untuk Meningkatkan Penjualan Pada Rute Jkt Pdg Jkt (Studi Kasus Pesawat Citylink) - Mustika Sari; Reni Dian Oktaviani (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
The purpose of this research is to find out the upcoming implementation, development and trend of JKT PDG JKT route of CityLink Airlines using the Allotment System. The problem of this study is the decreasing development of seat sales with the allotment system method. The method used in this study was a linear trend method to forecast sales in the following year. The results of this study are to use the Allotment System. The previous application of the seat allotment on CityLink flights is now no longer applied, because with many low-cost airline competition, all branches should try to sell as many seats as possible. The Padang branch and the Jakarta branch no longer sell tickets using the rationing system because it will reduce sales in other areas. Besides, with the existence of the global distribution system and computerized-system (CRS), and e-commerce, each customer could buy tickets easily though in areas that do not have branch representatives.